Synergistic Regulation of Schwann Cell Proliferation by Heregulin and Forskolin - Rahmatullah, Mohammed (American Society for Microbiology, 1998)
A peptide corresponding to the epidermal growth factor homology domain of β-heregulin stimulated autophosphorylation of the heregulin receptors erbB2 and erbB3 in Schwann cells and activation of the mitogen-activated protein (MAP) kinases ERK1 and ERK2. Heregulin-dependent activation of PAK65, a component of the stress-activated signaling pathway, ribosomal S6 kinase, and a cyclic AMP (cAMP) response element binding protein (CREB) kinase, identified as p95(RSK2), was also observed. Receptor phosphorylation and activation of these kinases in response to heregulin occurred in the absence of forskolin stimulation and were not augmented in cells treated with forskolin, a direct activator of adenylyl cyclase. Schwann cell proliferation in response to heregulin was observed only when the cells were also exposed to an agent that elevates cAMP levels. In the absence of heregulin, elevation of cAMP levels failed to stimulate Schwann cell proliferation. Forskolin significantly enhanced heregulin-stimulated expression of cyclin D and phosphorylation of the retinoblastoma gene product. In cells treated with both heregulin and forskolin there was a sustained accumulation of phospho-CREB, which was not observed in cells treated with either agent alone. Heregulin and forskolin synergistically activated transcription of a cyclin D promoter construct. These results demonstrate that heregulin-stimulated activation of MAP kinase is not sufficient to induce maximal Schwann cell proliferation. Expression of critical cell cycle regulatory proteins and cell division require activation of both heregulin and cAMP-dependent processes.